Socio-Economic Empowerment of Women through Micro-Finance - Josily Samuel,; L.B. Kunnal,; Susheela P. Sawkar,; K.V. Ashalata, (Journal of Agricultural Extension Management, 2025)
The Human Development Report in 1995 quoted that out of 1.3 billion poor people living in developing countries, 70 per cent are women. Poverty among rural women is growing faster than rural men. Women in India form 89 per cent of the informal and unrecognized sector. In India, women produce 30 per cent of the food commodities consumed by the country but earn only 10 per cent of income and own 10 per cent of the property or wealth of the country. The process of economic development would be incomplete and lopsided unless women are fully involved in the process. Emancipation of women is an essential pre-requisite for economic development and social progress of the nation. Empowerment is an active process of enabling women to realize their full identity and power in all spheres of life. The concept of women's empowerment was introduced at the international women's conference in 1985 at Nairobi